Distribution of soil algae at the monitoring sites in the vicinity of Syowa Station between austral summers of 1992/1993 and 1997/1998 - Ohtani,Shuji; Suyama,Kousuke; Yamamoto,Hiroki; Aridomi,Yukari; Itohm,Ritsuko; Fukuoka,Yoshiko (National Institute of Polar Research, 2000)
P(論文) Distribution of soil algae was studied in the vicinity of Syowa Station in Lutzow-Holm Bay, Antarctica between the austral summers of 1992/1993 (JARE-33) and 1997/1998 (JARE-38) from the viewpoint of environmental monitoring. Soils were collected from 10 monitoring sites. Sites 1-4 were within Syowa Station. Sites 1-3 were close to a urinal tank. Six sites (sites 5-10) were several km from the station. Site 10 was in a penguin rookery. Twenty-one soil algae were identified : eight of Cyanophyceae, eight of Chlorophyceae, three of Xanthophyceae and two of Bacillariophyceae. Leptolyngbya cf. battersii, Phormidium autumnale, Navicula muticopsis, Xanthonema spp., Botrydiopsis spp. and Macrochloris multinucleata were common. An ornithocoprophilous alga, Prasiola crispa, was found in cultures of soils from sites 1-3 and at site 10. Total carbon contents (TC), total nitrogen (TN) and total phosphorus (TP) in soils ranged from 0.04 to 0.991%, 0.002-0.401% and 0.161-0.809%, respectively. Maximum TC, TN and TP were observed at site 10. Relatively high values of TC (0.301%) and TN (0.016%) were detected at site 2. Presence of P. crispa at sites 1-3 and higher values of TC and TN at site 2 indicated that eutrophication of surface soils occurred near the urinal tank. The results of cluster analysis showed that most soil algal assemblages at sites 1-3 were grouped together. No clear changes in soil algal communities were observed during the study period at any of the monitoring sites. departmental bulletin paper